The influence of IMF clock angle on the cross section of the tail bow shock. Issue 11 (25th November 2016) - Wang, M.; Lu, J. Y.; Kabin, K.; Yuan, H. Z.; Ma, X.; Liu, Z.‐Q.; Yang, Y. F.; Zhao, J. S.; Li, G.
Abstract: We study effects of the interplanetary magnetic field (IMF) orientation on the terrestrial tail bow shock location and shape by using global MHD magnetosphere model and empirical bow shock models. It is shown that the tail bow shock cross section is well approximated by an ellipse with the direction of the major axis roughly perpendicular to the IMF clock angle direction. With the increasing IMF clock angle, the eccentricity of the bow shock cross section increases for northward IMF but decreases for southward IMF. Key Points: The tail BS cross section is well approximated by an ellipse with its major axis roughly perpendicular to the IMF clock angle direction For northward IMF, the eccentricity of the tail bow shock cross section increases with the IMF clock angle For southward IMF, the eccentricity of the tail bow shock cross section decreases with the IMF clock angle